The 2012 Senkaku Dispute: Origins and Lessons - I. V. Dyachkov (Vestnik MGIMO-Universiteta)
The recent Sino-Japanese conflict over the Senkaku (Diaoyu) Islands has turned the attention of the academic community toward growing nationalistic sentiment in North East Asia. This paper is an attempt to analyze the territorial dimension of the region’s nationalism, identify various factors that are bringing nationalism to the fore, warn of the possible dangers of using this political tool and make some short- and long-term predictions concerning the recent dispute.